2009
DOI: 10.1111/j.1472-765x.2008.02486.x
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic bacterial flora in root and stem tissues of black pepper (Piper nigrumL.) genotype: isolation, identification and evaluation againstPhytophthora capsici

Abstract: Aim: To isolate and identify black pepper (Piper nigrum L) associated endophytic bacteria antagonistic to Phytophthora capsici causing foot rot disease. Methods and Results: Endophytic bacteria (74) were isolated, characterized and evaluated against P. capsici. Six genera belong to Pseudomonas spp (20 strains), Serratia (1 strain), Bacillus spp. (22 strains), Arthrobacter spp. (15 strains), Micrococcus spp. (7 strains), Curtobacterium sp. (1 strain) and eight unidentified strains were isolated from internal ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(105 citation statements)
references
References 28 publications
1
100
0
4
Order By: Relevance
“…al., 2007Mano and Morisaki, 2008;Cottyn et al, 2009;Kaga et al, 2009;Ji et al, 2014;Nhu and Diep, 2014 (Barka et al, 2002;Oliveira et al, 2003;Kang et al, 2007;Szilagyi-Zecchin et al, 2014). In addition, endophytic bacteria have been reported to be involved with other mechanisms such as competition for place and food, and antibiosis (Sturz et al, 2000;Reiter et al, 2002;Compant et al, 2005;Aravind et al, 2009;Ji et al, 2013). Especially in rice, Ji et al (2013) found that treatment of rice seeds with the diazotrophic endophytes Paenibacillus, Microbacterium, Bacillus and Klebsiella, induced systemic resistance against Fusarium oxysporum and Rhizoctonia solani in addition to the growth induction of the rice plant.…”
Section: Discussionmentioning
confidence: 99%
“…al., 2007Mano and Morisaki, 2008;Cottyn et al, 2009;Kaga et al, 2009;Ji et al, 2014;Nhu and Diep, 2014 (Barka et al, 2002;Oliveira et al, 2003;Kang et al, 2007;Szilagyi-Zecchin et al, 2014). In addition, endophytic bacteria have been reported to be involved with other mechanisms such as competition for place and food, and antibiosis (Sturz et al, 2000;Reiter et al, 2002;Compant et al, 2005;Aravind et al, 2009;Ji et al, 2013). Especially in rice, Ji et al (2013) found that treatment of rice seeds with the diazotrophic endophytes Paenibacillus, Microbacterium, Bacillus and Klebsiella, induced systemic resistance against Fusarium oxysporum and Rhizoctonia solani in addition to the growth induction of the rice plant.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas is a well-known plant-associated bacterium found in the majority of plant species. These bacteria have been effective in the biological control of diverse diseases, such as foot rot in black pepper (Aravind et al, 2009) and grapevine gray mold caused by Botrytis cinerea (Verhagen et al, 2010). Additionally, Pseudomonas bacteria are considered plant growth-promoting bacteria (PGPB) due to many traits, which contribute to the growth and development of plants, such as the production of phytohormones and siderophores (Glick, 2012).…”
Section: Endophytic Bacteria Of P Tuberculatum Are Associated With Pmentioning
confidence: 99%
“…Antagonistic bacteria for the biological control of nursery wilt in black pepper were isolated by Anith et al (2003). In addition, Aravind et al (2009) isolated Bacillus and Pseudomonas bacteria that are effective in the biological control of Phytophthora capsici, the causal agent of the black pepper foot rot disease in India and other Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…Each 1g sample was added to 0.2% sterile water agar (90 mL), stirred using magnetic stirrer for 5 min, and serially diluted and the dilutions of 10 -6 and 10 -8 were plated in nutrient agar (NA) for bacterial counts and dilutions of 10 -3 and 10 -5 in Rose Bengal agar (RBA) for fungal counts. For enumerating the introduced bacteria, NA amended with selective antibiotics and TTC were used (Aravind et al 2008).…”
Section: Soil Sampling and Recording Of Observationsmentioning
confidence: 99%